Prevention of Venous Thromboembolism After Neurosurgery - Agnelli, Giancarlo (Thrombosis and Haemostasis, 1999)
The optimal strategy for the prevention of venous thromboembolism in patients undergoing neurosurgery has been a matter of debate for many years,1 and it is currently under review because of the results of recent clinical trials. This issue is, indeed, of particular clinical interest because of the neurosurgeons’ fear of bleeding complications, potentially associated with the use of anticoagulants, and the high incidence of venous thromboembolism. Preventing venous thromboembolism is of crucial importance in neurosurgery patients for reasons that go beyond its high incidence. The management of patients who develop venous thromboembolism immediately after neurosurgery is rather complicated, due to the risks connected with the administration of therapeutic doses of heparin and warfarin. In addition, the insertion of a vena caval filter, which is frequently required, is rather expensive and not without risk. Thus, in neurosurgery, even more than in other clinical settings, the optimal strategy for the management of venous thromboembolism is its prevention.The purpose of this paper is to review the epidemiology of venous thromboembolism in neurosurgery, its biological risk factors, and the results of clinical trials that have studied the prevention of venous thromboembolism in this clinical setting.